The Utility of Positron Emission Tomography in the Treatment Planning of Image-Guided Radiotherapy for Non-Small Cell Lung Cancer - Chi, Alexander; Nguyen, Nam P. (Frontiers in Oncology, 2014)
In the thorax, the extent of tumor may be more accurately defined with the addition of 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET) to computed tomography (CT). This led to the increased utility of FDG-PET or PET/CT in the treatment planning of radiotherapy for non-small cell lung cancer (NSCLC). The inclusion of FDG-PET information in target volume delineation not only improves tumor localization, but also decreases the amount of normal tissue included in the planning target volume (PTV) in selected patients. Therefore, it has a critical role in image guided radiotherapy (IGRT) for NSCLC. In this review, the impact of FDG-PET on target volume delineation in radiotherapy for NSCLC, which may increase the possibility of safe dose escalation with IGRT, the commonly used methods for tumor target volume delineation FDG-PET for NSCLC, and its impact on clinical outcome will be discussed.